Augmented reality mobile application for arabic text extraction, recognition and translation. Issue 4 (4th July 2018) - Saudagar, Abdul Khader Jilani; Mohammad, HabeebVulla
Abstract: People visit different countries in their life-time as a student, employee, pilgrim and tourists. They have to face many problems upon arriving to the new places. One major problem they face is the adaptability to the new environment and to overcome the language barrier. Understanding and communicating with the local people in their regional language is a difficult task for the new comer. The proposed research work develops an augmented reality mobile application which caters the community by offering a reliable service in the form of translating text. Developed application extracts text from the captured image using mobile camera and translates into the required target language. This application helps the people to understand signboards, banners etc., and results in easy navigation of people from one place to another. Tesseract optical character recognition (OCR) library for Arabic language is used in this work for developing the augmented reality mobile application to improve the quality and accuracy of Arabic text extraction, recognition and translation. To the researchers' knowledge the Tesseract OCR library for Arabic is ported first time to Android platform and its implementation outcomes achieves very promising results with a text extraction, recognition and translation rate of 90.2%.